From Obtaining to Degradation of PHB: Material Properties. Part I (2017)
This paper presents a review of the chemical, physical and morphological characteristics, as well as the existing applications and mechanisms for the production of poly (3-hydroxybutyrate). This biopolymer, which is obtained from renewable sources, degrades when exposed in biologically active environments and is biocompatible, that is, it is not rejected by the human body in health applications. However, in spite of presenting similar properties with some conventional plastics, the PHB exhibits fragile behavior and thermal instability when processed. The literature proposes the use of blends, the development of copolymers or the insertion of additives in an attempt to improve the mechanical and thermal properties of PHB.